Parasitic infections and their potential threat to blood safety: a literature review from Iran - Mardani, Ahmad (The Journal of Infection in Developing Countries, 2025)
Introduction: Transmission of parasitic agents through transfusion can endanger the availability of safe blood and blood components for patients in need. The aim of this research was to describe the current status of transfusion-transmitted parasitic infections (TTPIs) in Iran and propose strategies to minimize their transmission risk. Methodology: This narrative review included all studies that estimated the prevalence of TTPIs in Iranian blood donors based on parasitological, serological, and molecular techniques. A literature search was conducted for the period between 1960 and 2023 using medical subject headings (MeSH) terms in 11 English and Persian electronic databases. The extracted data were recorded on a pre-prepared checklist, and analyzed using SPSS. Results: Twenty-nine studies were eligible for inclusion. A total of 12,643 blood donors were examined for malaria, visceral leishmaniasis (VL), and toxoplasmosis in endemic and non-endemic areas. The overall serological prevalence of malaria, Leishmania infantum, and Toxoplasma gondii infections among blood donors was 9.60%, 1.96%, and 35.75%, respectively. The results of molecular techniques were positive in 0.71%, 39.22% (only seropositive samples), and 8.73% for malaria, VL, and toxoplasmosis, respectively. Conclusions: Considering the detection of parasitic DNA causing malaria, VL, and toxoplasmosis; and the presence of anti-T. gondii IgM antibodies among Iranian blood donors; their transmission through blood and blood components transfusion cannot be ruled out, particularly in endemic areas. Therefore, it is essential to adopt and implement appropriate strategies to minimize the risk of TTPIs and ensure the availability of safe and sufficient blood and blood components for patients in need.